Low serum cholesterol levels predict inferior prognosis and improve NCCN‐IPI scoring in diffuse large B cell lymphoma - Gao, Rui; Liang, Jin‐Hua; Wang, Li; Zhu, Hua‐Yuan; Wu, Wei; Cao, Lei; Fan, Lei; Li, Jian‐Yong; Yang, Tao; Xu, Wei (International journal of cancer, 2018)
Low circulating cholesterol concentration is associated with elevated cancer incidence and mortality. However, the association between cholesterol levels and diffuse large B cell lymphoma (DLBCL) remains unknown. The aim of our study was to evaluate the prognostic value of serum lipid profile in DLBCL. Five hundred and fifty enrolled subjects with detailed serum lipid levels at diagnosis of DLBCL were randomly divided into a training set (n = 367) and a validation set (n = 183) (ratio, 2:1). Multivariate Cox regression analyses screened the prognostic factors associated with progression‐free survival (PFS) and overall survival (OS). Performances of models were compared using C‐index and area under the curve in internal and external validation. The results showed that decreased levels of total cholesterol (TC), high‐density lipoprotein cholesterol (HDL‐C) and low‐density lipoprotein cholesterol (LDL‐C) were associated with unfavorable PFS and OS in the rituximab era, and concurrently low HDL‐C together with low LDL‐C was an independent prognostic indicator for both PFS and OS. Patients achieving complete remission or partial remission after 6–8 circles of chemotherapies had significantly increased cholesterol levels compared to the levels at DLBCL diagnosis, and HDL‐C or LDL‐C elevations were correlated with better survival. Furthermore, the predictive and discriminatory capacity of the National Comprehensive Cancer Network (NCCN)‐International Prognostic Index (IPI) together with low cholesterol levels was superior to NCCN‐IPI alone both in the training and validation set. In conclusion, serum cholesterol levels are simple and routinely tested parameters, which may be good candidates for predicting prognosis in the future clinical practice of DLBCL. What's new? Cholesterol is involved in the organization of the cytoskeleton, cell polarity and angiogenesis, but the role of lipid metabolism in cancer development is not yet fully explored. Here the authors show that low levels of high‐density HDL combined with low levels of low‐density LDL function as an independent prognostic indicator for progression‐free and overall survival in patients with B cell lymphoma (DLBCL). The results support the emerging notion that low cholesterol concentration is associated with elevated cancer incidence and underscore the use of simple cholesterol measurements as a prognostic marker in DLBCL.